The multidimensionality of food insecurity from the perspective of community health workers (Research, Society and Development, 2022)
This article presents part of the results of a subsequent master's thesis of an empirical study in a city of the Brazilian southeastern. Were conducted interviews with thirty-five Community Health Agents. The objective was to investigate the possible meanings of food insecurity from the perspective of Community Health Agents. The reports were transcribed and followed the content analysis proposed by Bardin, besides the use of data analysis Max-QDA software. The results were presented by two categories: (1) perceptions about the difficulty or ease of access to food; (2) complexity and multidimensionality of food insecurity. The speeches exposed vulnerabilities situations, injustices and difficulties experienced by local population that directly influence the maintenance of food insecurity. Bioethics proved to be a theoretical-practical field able to match the complexity of insecurity given the range of determinants and resulting factors that encompassed the stage of access to food.